PERAN GURU SEBAGAI ORANG TUA ROHANI BERDASARKAN SURAT I DAN II TIMOTIUS - Nelly Nelly; Femi Mariance Atonis (Institut Agama Kristen Negeri (IAKN) Ambon, 2021)
The role of teachers in the quality education process needs to be improved. This is because the quality of teacher service can produce quality graduates. As Jesus was known as the Great Teacher and formed His disciples to continue the relay of the great commission of service, so did the Apostle Paul, following in the footsteps of Jesus Christ, formed his protégé Timothy to become a good teacher of the church he served. This research is a literature review of Timothy's letter using descriptive methods about the role of teachers as spiritual parents and how teachers apply them. The conclusion is Paul's role as a spiritual parent for Timothy's protégé, namely as an educator, mentor, encouragement, role model and friend. The results of this study are recommended to be applied to SDK Philia Ambulu Jember teachers. Keywords: The Role Of Teachers, Christian Religious Educators, Timothy, Spiritual Parents